The magnetic properties of (La,Ce)Co5 ((La,Ce)=La0.35Ce0.65, La-Ce mischmetal) nanoflakes prepared by surfactant-assisted ball milling - X. Zhao; W. L. Zuo; D. Liu; J. F. Xiong; S. L. Zuo; Y. Zhang; X. Q. Zheng; F. X. Hu; T. Y. Zhao; J. R. Sun; B. G. Shen (AIP Advances, 2018)
The hard magnetic (La,Ce)Co5 nanoflakes with high coercivity and narrow thickness distribution have been successfully obtained by surfactant-assisted ball milling (SABM). The magnetic properties, morphology and interaction of (La,Ce)Co5 nanoflakes are studied in this work. The coercivity and remanence ratio of (La,Ce)Co5 nanoflakes are 5.48 kOe and 0.71, respectively. The X-ray powder diffraction (XRD) patterns indicate that the (La,Ce)Co5 nanoflakes are CaCu5-type hexagonal crystal structure. The average thickness and aspect ratio are 47 nm and 40, respectively. The intergrain interaction of the (La,Ce)Co5 nanoflakes is studied using the δm(H)-curves technique which shows the magnetostatic-dominated particle interaction. The high coercivity and narrow thickness distribution of (La,Ce)Co5 nanoflakes could be promising for the future development of the high performance soft/hard exchange spring magnets.